1984
DOI: 10.1073/pnas.81.13.4028
|View full text |Cite
|
Sign up to set email alerts
|

Insulin activates the appearance of insulin-like growth factor II receptors on the adipocyte cell surface.

Abstract: To evaluate the mechanism of insulin action to increase rat 2sI-labeled insulin-like growth factor II (125I- IGF 4028The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. §1734 solely to indicate this fact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…It has been shown by ligand binding studies that insulin causes translocation of IGF-II/Man-6-P receptors from an intracellular storage pool to the cell surface without increasing their affinity for IGF-II (18,19,32). Also, insulin stimulates internalization and degradation of IGF-II, whereas IGF-II itself does not have this effect (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown by ligand binding studies that insulin causes translocation of IGF-II/Man-6-P receptors from an intracellular storage pool to the cell surface without increasing their affinity for IGF-II (18,19,32). Also, insulin stimulates internalization and degradation of IGF-II, whereas IGF-II itself does not have this effect (27).…”
Section: Discussionmentioning
confidence: 99%
“…I-IGF-II binding studies (18,19,23), insulin causes a translocation from LM to PM fractions of a small portion of the IGF-II/ Man-6-P receptor in such a way that its amount in LM decreases to 67% and increases in PM to 20% of the total receptor content. The amount of this receptor in heavy microsomes does not change in response to insulin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Lawrence et al ( 13) and others (25) suggested that the okadaic acid-induced inhibition oftranslocation ofGLUT-4 is due to increased reinternalization of GLUT-4 in a phosphorylated form. Studies by Corvera and Czech (32) and others (33,34) showed that the insulin-like growth factor II (IGF II) receptor is translocated to the plasma membrane in response to insulin. Moreover, insulin causes a decrease in IGF II receptor phosphorylation in the plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin also stimulates the net exocytosis of the cationindependent mannose-6-phosphate receptor (CI͞M6PR), which is located in a distinct vesicular compartment (31,32). CI͞M6PR traffics between the trans-Golgi network, late endosomes, and lysosomes, distinct from the GLUT4͞IRAP-containing compartments (33).…”
Section: Overexpression Of Cap⌬soho In 3t3-l1 Adipocytes Specificallymentioning
confidence: 99%